Studies on Prevalence and Outbreak of Ectoparasites in Native Chickens in Central Part of Thailand - Arkom Sangvaranond (Agriculture and Natural Resources, 1993)
Studies on incidence and outbreak of ectoparasites occurring in adult native chickens by examination of 1781 fowls (662 males and 1119 females, 1-4 years old) from 39 amphoes and 151 districts of 6 provinces in central part of Thailand during 1989-1992 revealed incidence of the following ectoparasites; nine species of biting lice, Menopon gallinae 89.3 %, Menacanthus pallidulus 3.9 %, Menacanthus stramineus3.8 %,unidentifiedamblycerans(Menoponspp.) 5.4 %, Lipeurus caponis 75.8 %, Oxylipeurus dentatus 2.1 %, Goniocotes gallinae 7.6%, Goniodes dissimilis 5.1% and Chelopistes meleagridis 0.7%, one species offleas, Echidnophaga gallinacea 5.3% ; one species of ticks, Haemaphysalis (Kaiseriana) wellingtoni 0.2%; five species of mites, Dermanyssus gallinae 4.1%, Ornithonyssus bursa 9.9%, Megninia cubitalis 6.2%, Pterolichus obtusus 42.7% and Knemidocoptes mutans. In addition, fauna and incidence of ectoparasites in various amphoes and provinces in central part of Thailand were also reported in this study.